2010
DOI: 10.1111/j.1365-2796.2010.02281.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and risk of cognitive decline: a meta-analysis of prospective studies

Abstract: Abstract. Sofi F, Valecchi D, Bacci D, Abbate R, Gensini GF, Casini A, Macchi C (Centro S. Maria agli Ulivi, Onlus IRCCS; Thrombosis Centre, University of Florence; Azienda Ospedaliero-Universitaria Careggi, Florence, Italy). Physical activity and risk of cognitive decline: a meta-analysis of prospective studies. J Intern Med 2011; 269: 107-117.Objective. The relationship between physical activity and cognitive function is intriguing but controversial. We performed a systematic meta-analysis of all the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
645
4
47

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 949 publications
(730 citation statements)
references
References 25 publications
34
645
4
47
Order By: Relevance
“…[28][29][30][31] Clinical trials 32 Non-pharmacological measures, such as physical activity, are also important and have been identified to have beneficial effects on cognition as well as protective benefits on brain plasticity in vascular CI and related conditions. 33,34 The main task for physicians is to identify patients with early stages of CI in order to start corrective measures as soon as possible and also manage patients at risk of CI. …”
Section: Importance Of Cognitive Decline For Prognosis and Self-carementioning
confidence: 99%
“…[28][29][30][31] Clinical trials 32 Non-pharmacological measures, such as physical activity, are also important and have been identified to have beneficial effects on cognition as well as protective benefits on brain plasticity in vascular CI and related conditions. 33,34 The main task for physicians is to identify patients with early stages of CI in order to start corrective measures as soon as possible and also manage patients at risk of CI. …”
Section: Importance Of Cognitive Decline For Prognosis and Self-carementioning
confidence: 99%
“…The long-term benefits of PA on neurocognitive outcomes among HIV-uninfected older adults are well established [10][11][12]. Epidemiological studies have indicated that midlife PA is associated with a lower risk of neurocognitive decline and dementia later in life [13,14]. Moreover, PA intervention trials have consistently shown improved cognitive function in older HIV-uninfected adults who participate in aerobic activity as compared to control groups [10,[15][16][17][18][19][20].…”
mentioning
confidence: 99%
“…Populationbased studies of older adults have reported a slower rate of decline in cognitive function among those engaged in higher levels of physical activity at baseline (Ku et al 2012;Lytle et al 2004;Weuve et al 2004;Yaffe et al 2001). In a meta-analysis of prospective studies involving people aged 65 years and older, physical activity at both high and low-to-moderate levels was found to lower the risk of cognitive decline (Sofi et al 2011). In addition, physical exercise training of older adults has shown some promise in enhancing cognitive vitality (Colcombe and Kramer 2003;Kirk-Sanchez and McGough 2014).…”
Section: Introductionmentioning
confidence: 99%